2019
DOI: 10.1021/acssuschemeng.9b02594
|View full text |Cite
|
Sign up to set email alerts
|

Starch Nanoparticles–Graphene Aerogels with High Supercapacitor Performance and Efficient Adsorption

Abstract: In this work, graphene oxide (GO) nanosheets are combined with dialdehyde starch nanocrystals (DASNCs) to form highly porous, mechanically robust, compressible aerogels, which can be used as supercapacitor electrodes and efficient adsorbents. The introduction of the DASNC to GO was confirmed by SEM, TEM, FTIR, Raman, XPS, and TGA. After DASNCs attached to the reduced graphene (RGO), the aerogel skeleton became more robust, resulting in high mechanical properties. DASNC can effectively prevent irreversible self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Among the reported sustainable materials used in FEs, starch have advantages on the acceptable solubility in water, good property of film forming and relative low cost comparing with cellulose, lignin and proteins. Therefore, a lot of efforts have been put into the developments of FEs based on starch [37][38][39][40][41] , in which the starch usually appeared as films or gels. The starch films were often used as soft and transparent substrates because of the intrinsic good film-forming property of starch.…”
Section: Introductionmentioning
confidence: 99%
“…Among the reported sustainable materials used in FEs, starch have advantages on the acceptable solubility in water, good property of film forming and relative low cost comparing with cellulose, lignin and proteins. Therefore, a lot of efforts have been put into the developments of FEs based on starch [37][38][39][40][41] , in which the starch usually appeared as films or gels. The starch films were often used as soft and transparent substrates because of the intrinsic good film-forming property of starch.…”
Section: Introductionmentioning
confidence: 99%
“…HES polymers require crosslinking to improve features like stability and sturdiness. In the literature in recent times, there are very few studies about GO-starch-based composites and some of these examined applications as membrane ltering [18], drug delivery system [19] and adsorption [20,21]. Another study reported a nanocomposite comprising starch, polyacrylamide and poly(2-acrylamido-2-methylpropane sulfonic acid) including GO layers for methylene blue adsorption [22].…”
Section: Introductionmentioning
confidence: 99%
“…These graphemic materials are chemically grafted or covalently functionalized with other organic and inorganic molecules (nanohybrids) [ 5 ] to be used as raw material in the manufacturing of solar cells [ 6 ], battery electrodes [ 7 ], biosensors [ 8 ], and prostheses [ 9 ], among others [ 10 , 11 ], where graphite and GO considerably improve the performance of the products. Nanohybrids grafted with organic molecules, as starch and fructose, are used due to their biodegradation [ 12 , 13 ] and biocompatibility as material for antibiotic recovery in milk [ 14 ], manufacturing of antimicrobial films for foods [ 15 , 16 ], formulation of bio-nano-compounds [ 17 , 18 , 19 , 20 , 21 , 22 ], supercapacitors [ 23 , 24 , 25 , 26 ], fuel cells [ 27 ], water purification membranes [ 28 , 29 , 30 ], biosensors [ 31 , 32 ], adhesives [ 33 ], and bone implants [ 34 ]. To synthetize these GO/starch [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] and GO/fructose [ 27 ] nanohybrids, chemical processes include exfoliated graphite by sonication in an aqueous medium or polar solvent for several hours.…”
Section: Introductionmentioning
confidence: 99%